2016
DOI: 10.1155/2016/3145343
|View full text |Cite
|
Sign up to set email alerts
|

A Bilateral Traumatic Hip Obturator Dislocation

Abstract: A case of a bilateral simultaneous traumatic obturator dislocation of both hip joints in an 18-year-old young man following a traffic accident is presented. We reduced the dislocated femoral heads immediately under general anesthesia followed by passive and active exercises and early full-weight bearing mobilization. After 5 years, the result was excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A simultaneous traumatic anterior hip dislocation of the obturator type is an extremely rare injury. The greater trochanter impinges on the acetabular rim which acts as a lever and pushes the femoral head out anteriorly [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A simultaneous traumatic anterior hip dislocation of the obturator type is an extremely rare injury. The greater trochanter impinges on the acetabular rim which acts as a lever and pushes the femoral head out anteriorly [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdulfattah Abdullah et al[ 14 ] reported that the patient should rest in bed for three weeks, and use an T-shaped pillow, then remove the traction and start physical therapy. Karaarslan et al[ 15 ] concluded that successful treatment, early full-load mobilization, and early passive motion plus active auxiliary motion were very useful.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anterior hip dislocations are more infrequent than posterior dislocations[ 20 ], accounting for up to 13% of all hip dislocations[ 21 ]. Anterior dislocation occurs as a result of a force acting on an abducted hip joint, which is then flexed and externally rotated to dislocate the femoral head forward[ 22 , 23 ]. The eventual position of the femoral head is determined by the degree of flexion at the time of injury.…”
Section: Discussionmentioning
confidence: 99%
“…According to Epstein’s classification, the anterior dislocation can be divided into pubic (type I) and obturator (type II) dislocation[ 2 ]. Obturator dislocation, which represents 2%-5% of all hip dislocations[ 7 ], is the most rare type of hip dislocation and is usually caused by falls[ 22 ]. As was the case in our report, obturator dislocation occurs when a force is transmitted from the knee to the femoral head while the limb is in a position of extreme flexion, abduction, and lateral rotation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation